A high-performance composite aerogel structural material for foldable assembled buildings, a preparation method and applications thereof
Through the technical means of frozen casting and high-temperature silicon carbide formation, the problem of insufficient mechanical strength of aerogel materials is solved, and a lightweight porous material with high strength and excellent thermal insulation performance is achieved, which is suitable for insulation applications in folded prefabricated buildings.
Patent Information
- Application Number
- CN202410928379.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-11
AI Technical Summary
When used as building insulation materials, existing aerogel materials have low mechanical strength and high brittleness, making it difficult to meet the high performance needs of folded prefabricated buildings.
The pores are grown in a direction through frozen casting technology to form anisotropic porous material, and silicon carbide is formed at high temperatures, combining with the layered structure of white carbon black to improve the strength and thermal insulation properties of the material.
It significantly improves the strength of the material to 3-4 times the unfired while maintaining lightweight and excellent thermal insulation properties, and is suitable for insulation materials for folding prefabricated buildings.
Smart Images

Figure CN118851719B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal insulation material preparation, and specifically relates to a high-performance composite aerogel structural material for foldable assembled buildings, a preparation method and applications thereof. Background Art
[0002] White carbon black is also called hydrated silicon dioxide, with the chemical formula of SiO 2 ·nH 2 O, it is a white, non-toxic, amorphous fine powder inorganic silicon compound, which has many good properties and is widely used in many fields such as plastics, rubber, papermaking, coatings, dyes and inks. It has excellent prospects in the preparation of ultra-light materials. Common methods for preparing aerogels include sol-gel method, supercritical drying method and template method. These methods can be selected and adjusted according to the required aerogel performance and application requirements to achieve precise control of aerogel structure and performance.
[0003] As an emerging structural system developed from industrial design, mechanical design, and aviation design, folding and prefabricated buildings have the characteristics of mobility, controllability, and assembly. Folding and prefabricated buildings can shorten the construction time, have no disassembly and assembly losses, are green and environmentally friendly, and have rich combinations. They have great advantages in transportation costs, use costs, and storage costs. They are an important driving force for the sustainable development of the construction industry and the realization of dual carbon goals. They can play an important role in application scenarios such as military supplies, cultural tourism, camping, medical care, emergency, commerce, and infrastructure. New insulation materials promote the development of folding buildings in the direction of high performance, greening, and other sustainable directions.
[0004] Compared with traditional insulation materials, aerogel materials have the characteristics of low density, low thermal conductivity, super hydrophobicity, and non-toxicity. They can be used as lightweight and efficient insulation materials. However, their mechanical strength is low, and they are brittle and easy to break, which limits their application as building insulation materials. Summary of the invention
[0005] The purpose of the present invention is to prepare a lightweight porous high-performance thermal insulation material, and to propose a high-performance composite aerogel structural material for foldable assembled buildings, a preparation method and an application thereof.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings comprises the following steps:
[0008] Step 1. Weigh a certain mass of white carbon black and water-soluble biochar according to the molar ratio, mix them evenly and add them to a mixed solution of a surfactant and deionized water to obtain a mixed solution, stir the mixed solution at a speed of 800-1200 rpm for 7-9 hours to obtain a suspension for standby use;
[0009] Step 2. Weigh a certain volume of the suspension obtained in step S1, and pour it into a silica gel container placed on top of a copper rod, the copper rod is placed in a double-layer vacuum insulation container, and liquid nitrogen is added to the double-layer vacuum insulation container to cool the copper rod. After cooling for 5-10 minutes, the suspension forms a frozen composite block material containing oriented ice crystals, which is ready for use;
[0010] Step 3. Place the frozen composite block material obtained in step 2 into a freeze dryer for freeze drying to obtain a self-supporting scaffold structure material with micro-scale pores arranged in a spatial hierarchical manner for standby use;
[0011] Step 4. Place the self-supporting support structure material with spatial hierarchically arranged micro-scale pores obtained in step S3 in a tubular furnace, and perform a high-temperature reaction under the protection of argon to obtain a lightweight, porous, high-performance structural material based on silica.
[0012] Furthermore, in step 1, the molar ratio of white carbon black to water-soluble biochar is 4.0-3.0:1, the volume ratio of surfactant to deionized water is 1:3, and the solid-liquid ratio of white carbon black to the mixed solution is 100-150 mg:1 ml.
[0013] Furthermore, in step 2, the style of the silica gel container is a cylindrical container with a bottom diameter of 2 cm and a height of 2 cm, the volume of the suspension added is 6 ml, the volume of liquid nitrogen added is 300-350 ml, and the temperature of the top of the copper rod is controlled between -80°C and -100°C.
[0014] Furthermore, the instrument model used for freeze drying in step 3 is SCIENTZ-10YG / A, and the silicone oil temperature is set to 9°C, the ambient temperature is 24.5°C, the cold trap temperature is -60°C, and the box is vacuum.
[0015] Furthermore, in step 4, the rate of introducing argon into the tubular furnace is 300-500 ml / min, the tubular furnace is heated to 700-850°C at a heating rate of 10-20°C / min, maintained for 1 hour, and then continued to be heated to 1450-1500°C at a heating rate of 10-20°C / min and maintained for 2 hours, and finally reduced to 1000°C at a rate of 5°C / min, and then cooled to room temperature with the furnace.
[0016] A method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings. The prepared high-performance composite aerogel structural material for foldable and assembled buildings has a layered bonding structure of silicon carbide and white carbon black.
[0017] A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings and an application of the prepared high-performance composite aerogel structural material for foldable assembled buildings are used in the field of thermal insulation materials.
[0018] Furthermore, it can be used as the insulation material for the next generation of movable building foldable assembled building envelope systems.
[0019] The beneficial effects of the present invention are:
[0020] The method for preparing a high-performance composite aerogel structural material for foldable assembled buildings described in the present invention utilizes freeze casting to allow pores to grow in a directional manner to form an anisotropic porous material; simultaneously utilizes high-temperature cracking to create a carbon source for the formation of silicon carbide; and also utilizes the formation of silicon carbide to allow the porous material to obtain a certain strength.
[0021] The present invention discloses a method for preparing a high-performance composite aerogel structural material for foldable assembled buildings, which utilizes freeze casting to form a silica frame containing directional pores inside, and reacts the C on the surface with silica to generate silicon carbide at a specific temperature, thereby forming a layered bonding structure of silicon carbide and silica, which greatly increases the strength of the original frame and can be increased to 3-4 times that of the unfired frame.
[0022] The invention discloses a method for preparing a high-performance composite aerogel structural material for foldable assembled buildings, and the produced white carbon black lightweight porous material has high strength and good thermal stability. The porous structure of the material gives it excellent thermal insulation and lightweight properties, and is suitable for a variety of industrial applications, such as thermal insulation materials, filters, and catalyst carriers.
[0023] The method for preparing a high-performance composite aerogel structural material for foldable assembled buildings described in the present invention uses freeze casting technology to form a porous structure by controlling the directional growth of ice crystals. This process does not use harmful chemicals and is more environmentally friendly than traditional methods.
[0024] The method for preparing a high-performance composite aerogel structural material for foldable assembled buildings described in the present invention precisely controls the pore structure and microstructure of the material by performing staged heating at specific temperatures, thereby optimizing the physical and chemical properties of the material.
[0025] The method for preparing a high-performance composite aerogel structural material for foldable assembled buildings described in the present invention has freeze drying and segmented heating processes designed to be more efficient, which helps to reduce production costs and energy consumption.
[0026] The present invention discloses a method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings. The prepared high-performance composite aerogel structural material based on white carbon black has the characteristics of light weight and high strength, low thermal conductivity, excellent thermal insulation performance, etc., and integrates thermal insulation and structure. Compared with traditional thermal insulation materials such as polystyrene boards and polyurethanes, it has the advantages of high temperature resistance and fire prevention, green environmental protection, non-toxicity and renewability. This material can be used as an insulation material for the next generation of movable building foldable and assembled building enclosure systems, and is suitable for temporary or long-term use of foldable and assembled composite buildings for residential buildings, public infrastructure, emergency relief and military, etc., to achieve the recycling of foldable and assembled buildings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a photograph of the material prepared by the method of the present invention before the freeze-drying step;
[0028] Figure 2 is a photograph of the material prepared by the method of the present invention after the freeze-drying step;
[0029] Figure 3 This is a photo of a high-performance composite aerogel structural material for foldable assembled buildings according to the present invention;
[0030] Figure 4 This is a photo of the high-performance composite aerogel structural material for foldable assembled buildings described in the present invention under a heavy object. DETAILED DESCRIPTION Specific implementation method one:
[0032] A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings comprises the following steps:
[0033] Step 1. Weigh a certain mass of white carbon black and water-soluble biochar according to the molar ratio, mix them evenly and add them to a mixed solution of a surfactant and deionized water to obtain a mixed solution, stir the mixed solution at a speed of 800 rpm for 7 hours to obtain a suspension for standby use;
[0034] Furthermore, in step 1, the molar ratio of white carbon black to water-soluble biochar is 4.0:1, the volume ratio of surfactant to deionized water is 1:3, and the solid-liquid ratio of white carbon black to the mixed solution is 100 mg:1 ml;
[0035] Furthermore, the water-soluble biochar is sucrose, and the surfactant is anhydrous ethanol;
[0036] Step 2. Weigh a certain volume of the suspension obtained in step S1, and pour it into a silica gel container placed on top of a copper rod, the copper rod is placed in a double-layer vacuum insulation container, and liquid nitrogen is added to the double-layer vacuum insulation container to cool the copper rod. After cooling for 5-10 minutes, the suspension forms a frozen composite block material containing oriented ice crystals, which is ready for use;
[0037] Furthermore, in step 2, the style of the silica gel container is a cylindrical container with a bottom diameter of 2 cm and a height of 2 cm, the volume of the suspension added is 6 ml, the volume of the liquid nitrogen added is 300 ml, and the temperature of the top of the copper rod is controlled between -80°C and -100°C;
[0038] Step 3. Place the frozen composite block material obtained in step 2 into a freeze dryer for freeze drying to obtain a self-supporting scaffold structure material with micro-scale pores arranged in a spatial hierarchical manner for standby use;
[0039] Furthermore, the model of the instrument used for freeze drying in step 3 is SCIENTZ-10YG / A, and the silicone oil temperature is set to 9°C, the ambient temperature is 24.5°C, the cold trap temperature is -60°C, and the box is vacuum;
[0040] Step 4. placing the self-supporting support structure material with spatial hierarchically arranged micro-scale pores obtained in step S3 in a tube furnace, and performing a high-temperature reaction under the protection of argon gas to obtain a lightweight porous high-performance structural material based on white carbon black;
[0041] Further, in step 4, the rate of introducing argon into the tubular furnace is 300 ml / min, the tubular furnace is heated to 700°C at a heating rate of 10°C / min, maintained for 1 hour, and then continued to be heated to 1450°C at a heating rate of 10°C / min and maintained for 2 hours, and finally decreased to 1000°C at a rate of 5°C / min, and then cooled to room temperature with the furnace;
[0042] The method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings described in this embodiment is a high-performance composite aerogel structural material for foldable and assembled buildings, which has a layered bonding structure of silicon carbide and white carbon black.
[0043] The method for preparing a high-performance composite aerogel structural material for foldable assembled buildings described in this embodiment is a high-performance composite aerogel structural material for foldable assembled buildings, and the density is 0.173g / cm 3 .
[0044] A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings described in this embodiment is a method for preparing a high-performance composite aerogel structural material for foldable assembled buildings. Photos of the preparation process and product photos are shown in FIG. Figures 1 to 3As shown, the photo of the high-performance composite aerogel structural material for foldable assembled buildings under the pressure of heavy objects is shown in Figure 4 As shown, Figure 4 The mass of the high-performance composite aerogel structural material for foldable assembled buildings is 2.945 g, and the mass of the heavy crucible is 79.99 g, indicating that the high-performance composite aerogel structural material for foldable assembled buildings prepared in this embodiment has high structural strength.
[0045] A high-performance composite aerogel structural material for foldable and assembled buildings prepared by a method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings described in this embodiment has anisotropic thermal insulation properties. The heat transfer behavior was studied by observing the heat flow in the radial and axial directions respectively, and good thermal insulation performance was shown in the radial direction. The different heat transfer behaviors along the two main directions confirmed the anisotropy of thermal conductivity, which is similar to the heat transfer of other anisotropic insulators. The thermal conductivities measured in the radial and axial directions are approximately 11 and 35 mW / m·K, respectively, and the anisotropy coefficient is approximately 3.1. In particular, the radial thermal conductivity value is comparable to that of reported thermal superinsulating materials, such as graphene aerogel and silica aerogel, highlighting its excellent thermal insulation performance.
[0046] A method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings described in this embodiment is a high-performance composite aerogel structural material for foldable and assembled buildings. Thermal stability and chemical stability are another key criterion for evaluating the safety of thermal insulation materials. Isothermal treatment at 1000°C in an air furnace demonstrated good thermal oxidation stability. There was no significant change in the macroscopic morphology after the sample was treated for 30 minutes or more. The aerogel was further subjected to a butane blowtorch to simulate an erosive environment with a maximum temperature above 1200°C. It is worth noting that, except for some surface ablation marks observed in the SEM images, the macroscopic morphology remained almost unchanged after treatment for more than 30 minutes. This good resistance to thermal oxidation and corrosion is mainly attributed to SiC@SiO 2 Excellent chemical stability of composite materials.
[0047] A high-performance composite aerogel structural material for foldable and assembled buildings prepared by a method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings described in this embodiment, the aerogel exhibits rigid deformation behavior in the axial direction. The compressive stress-strain curve shows four deformation stages: a linear elastic state within 2.5% strain, a nonlinear elastic state between 2.5% and 7% strain, a plastic yield platform between 7% and 28% strain, and a densification process after 28% strain. The compression modulus calculated in the linear elastic state is about 160.8 kPa, and the specific modulus is 16.1 kN·m / kg, which is significantly higher than many other ultra-light materials with random microstructures. Specific implementation method 2:
[0049] A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings comprises the following steps:
[0050] Step 1. Weigh a certain mass of white carbon black and water-soluble biochar according to the molar ratio, mix them evenly and add them to a mixed solution of a surfactant and deionized water to obtain a mixed solution, stir the mixed solution at a speed of 1200 rpm for 9 hours to obtain a suspension for standby use;
[0051] Furthermore, in step 1, the molar ratio of white carbon black to water-soluble biochar is 3.0:1, the volume ratio of surfactant to deionized water is 1:3, and the solid-liquid ratio of white carbon black to the mixed solution is 150 mg:1 ml;
[0052] Furthermore, the water-soluble biochar is sucrose, and the surfactant is anhydrous ethanol;
[0053] Step 2. Weigh a certain volume of the suspension obtained in step S1, and pour it into a silica gel container placed on top of a copper rod, the copper rod is placed in a double-layer vacuum insulation container, and liquid nitrogen is added to the double-layer vacuum insulation container to cool the copper rod. After cooling for 5-10 minutes, the suspension forms a frozen composite block material containing oriented ice crystals, which is ready for use;
[0054] Furthermore, in step 2, the style of the silica gel container is a cylindrical container with a bottom diameter of 2 cm and a height of 2 cm, the volume of the suspension added is 6 ml, the volume of the liquid nitrogen added is 350 ml, and the temperature of the top of the copper rod is controlled between -80°C and -100°C;
[0055] Step 3. Place the frozen composite block material obtained in step 2 into a freeze dryer for freeze drying to obtain a self-supporting scaffold structure material with spatial hierarchically arranged micro-scale pores for standby use;
[0056] Furthermore, the model of the instrument used for freeze drying in step 3 is SCIENTZ-10YG / A, and the silicone oil temperature is set to 9°C, the ambient temperature is 24.5°C, the cold trap temperature is -60°C, and the box is vacuum;
[0057] Step 4. placing the self-supporting support structure material with spatial hierarchically arranged micro-scale pores obtained in step S3 in a tube furnace, and performing a high-temperature reaction under the protection of argon gas to obtain a lightweight porous high-performance structural material based on white carbon black;
[0058] Further, in step 4, the rate of introducing argon into the tubular furnace is 500 ml / min, the tubular furnace is heated to 850°C at a heating rate of 20°C / min, maintained for 1 hour, and then continued to be heated to 1500°C at a heating rate of 20°C / min and maintained for 2 hours, and finally decreased to 1000°C at a rate of 5°C / min, and then cooled to room temperature with the furnace;
[0059] The method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings described in this embodiment is a high-performance composite aerogel structural material for foldable and assembled buildings, which has a layered bonding structure of silicon carbide and white carbon black. Specific implementation method three:
[0061] A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings comprises the following steps:
[0062] Step 1. Weigh a certain mass of white carbon black and water-soluble biochar according to the molar ratio, mix them evenly and add them to a mixed solution of a surfactant and deionized water to obtain a mixed solution, stir the mixed solution at a speed of 1000 rpm for 8 hours to obtain a suspension for standby use;
[0063] Furthermore, in step 1, the molar ratio of white carbon black to water-soluble biochar is 3.5:1, the volume ratio of surfactant to deionized water is 1:3, and the solid-liquid ratio of white carbon black to the mixed solution is 120 mg:1 ml;
[0064] Furthermore, the water-soluble biochar is sucrose, and the surfactant is anhydrous ethanol;
[0065] Step 2. Weigh a certain volume of the suspension obtained in step S1, and pour it into a silica gel container placed on top of a copper rod, the copper rod is placed in a double-layer vacuum insulation container, and liquid nitrogen is added to the double-layer vacuum insulation container to cool the copper rod. After cooling for 5-10 minutes, the suspension forms a frozen composite block material containing oriented ice crystals, which is ready for use;
[0066] Furthermore, in step 2, the style of the silica gel container is a cylindrical container with a bottom diameter of 2 cm and a height of 2 cm, the volume of the suspension added is 6 ml, the volume of the liquid nitrogen added is 320 ml, and the temperature of the top of the copper rod is controlled between -80°C and -100°C;
[0067] Step 3. Place the frozen composite block material obtained in step 2 into a freeze dryer for freeze drying to obtain a self-supporting scaffold structure material with spatial hierarchically arranged micro-scale pores for standby use;
[0068] Furthermore, the model of the instrument used for freeze drying in step 3 is SCIENTZ-10YG / A, and the silicone oil temperature is set to 9°C, the ambient temperature is 24.5°C, the cold trap temperature is -60°C, and the box is vacuum;
[0069] Step 4. placing the self-supporting support structure material with spatial hierarchically arranged micro-scale pores obtained in step S3 in a tube furnace, and performing a high-temperature reaction under the protection of argon gas to obtain a lightweight porous high-performance structural material based on white carbon black;
[0070] Further, in step 4, the rate of introducing argon into the tubular furnace is 400 ml / min, the tubular furnace is heated to 800°C at a heating rate of 15°C / min, maintained for 1 hour, and then continued to be heated to 1460°C at a heating rate of 15°C / min and maintained for 2 hours, and finally decreased to 1000°C at a rate of 5°C / min, and then cooled to room temperature with the furnace;
[0071] The method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings described in this embodiment is a high-performance composite aerogel structural material for foldable and assembled buildings, which has a layered bonding structure of silicon carbide and white carbon black. Specific implementation method four:
[0073] A method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings as described in specific embodiments one to three, and an application of a high-performance composite aerogel structural material for foldable and assembled buildings, are used in the field of thermal insulation materials.
[0074] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0075] Although the present application has been described above with reference to specific embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, as long as there is no structural conflict, the various features in the specific embodiments disclosed in the present application may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A method for preparing a high-performance composite aerogel structural material for foldable assembled buildings, characterized in that: The steps include: Step 1. Weigh a certain mass of white carbon black and water-soluble biochar according to the molar ratio, mix them evenly and add them to a mixed solution of a surfactant and deionized water to obtain a mixed solution, stir the mixed solution at a speed of 800-1200 rpm for 7-9 hours to obtain a suspension for standby use; Step 2. Weigh a certain volume of the suspension obtained in step 1, and pour it into a silica gel container placed on top of a copper rod, the copper rod is placed in a double-layer vacuum insulation container, and liquid nitrogen is added to the double-layer vacuum insulation container to cool the copper rod. After cooling for 5-10 minutes, the suspension forms a frozen composite block material containing oriented ice crystals, which is set aside; Step 3. Place the frozen composite block material obtained in step 2 into a freeze dryer for freeze drying to obtain a self-supporting scaffold structure material with spatial hierarchically arranged micro-scale pores for standby use; Step 4. placing the self-supporting support structure material with spatial hierarchically arranged micro-scale pores obtained in step 3 in a tube furnace, and performing a high-temperature reaction under the protection of argon gas to obtain a lightweight porous high-performance structural material based on white carbon black; In step 1, the molar ratio of white carbon black to water-soluble biochar is 4.0-3.0:1, the volume ratio of surfactant to deionized water is 1:3, and the material-liquid ratio of white carbon black to the mixed solution is 100-150 mg:1 ml; The water-soluble biochar is sucrose, and the surfactant is anhydrous ethanol; In step 2, the style of the silica gel container is a cylindrical container with a bottom diameter of 2 cm and a height of 2 cm, the volume of the suspension added is 6 ml, the volume of the liquid nitrogen added is 300-350 ml, and the temperature of the top of the copper rod is controlled between -80°C and -100°C; In step 4, the rate of argon gas introduced into the tubular furnace is 300-500 ml / min, the tubular furnace is heated to 700-850°C at a heating rate of 10-20°C / min, maintained for 1 hour, then continued to heat to 1450-1500°C at a heating rate of 10-20°C / min and maintained for 2 hours, and finally decreased to 1000°C at a rate of 5°C / min, and then cooled to room temperature with the furnace.
2. The method for preparing a high-performance composite aerogel structural material for foldable assembled buildings according to claim 1, characterized in that: The instrument model used for freeze drying in step 3 is SCIENTZ-10YG / A, and the silicone oil temperature is set to 9°C, the ambient temperature is 24.5°C, the cold trap temperature is -60°C, and the box is vacuum.
3. A method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings according to any one of claims 1 to 2, wherein the high-performance composite aerogel structural material for foldable and assembled buildings is prepared, characterized in that: It has a layered structure of silicon carbide and white carbon black.
4. An application of a high-performance composite aerogel structural material for foldable and assembled buildings prepared by the method for preparing a high-performance composite aerogel structural material for foldable and assembled buildings as claimed in any one of claims 1 to 2, characterized in that: Used in the field of thermal insulation materials.
Citation Information
Patent Citations
Preparation method of high-temperature-resistant silicon carbide aerogel with directional hole structure
CN113651328A